Interaction between Community and Local Government in Evaluation Policy of Regional Regulation about Funeral Service Retribution - Kurniasih, Dewi; Thohir, Abdillah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Retribution is a regional collection as payment for services or the granting of certain permits from the regional government to individuals or entities. Bandung City TPU has a mismatch of funeral retribution rates with Bandung City regulations and burial grounds that are not in accordance with the Bandung City Data Portal. In evaluation the policy, its need a good interaction between community and local Government in implementation that policy. The aims of this study is to know interaction between community and Government in evaluation the policy of regional regulation of Bandung City Number 3 of 2017 about Cemetery Service Fees in Bandung City. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques used in this study through, observation, interviews and documentation. The results of this study indicate that the interaction between community and Local Government in evaluation the policy of regional regulation of Bandung City Number 3 of 2017 about Cemetery Service Fees in Bandung City is quite effective, these results were obtained through interviews with resource persons from TPU Pandu, TPU RancaciIi, TPU Maleer, TPU Cikutra and TPU Astana Anyar. By coordinating between TPU officers, the Cipta Karya, Construction Development and Spatial Planning and people who use TPU, it is hoped that there wiII be an increase in effectiveness.